2012
DOI: 10.1093/eurheartj/ehs431
|View full text |Cite
|
Sign up to set email alerts
|

Genetically elevated non-fasting triglycerides and calculated remnant cholesterol as causal risk factors for myocardial infarction

Abstract: These data are consistent with a causal association between elevated levels of remnant cholesterol in hypertriglyceridaemia and an increased risk of MI. Limitations include that remnants were not measured directly, and that APOA5 genetic variants may influence other lipoprotein parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
245
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(275 citation statements)
references
References 57 publications
10
245
0
3
Order By: Relevance
“…We have previously demonstrated that elevated remnant cholesterol is causally associated with increased risk of IHD and that this association is independent of low high-density lipoprotein cholesterol levels. 1,2 The causal association of nonfasting remnant cholesterol with low-grade inflammation observed in this study could be explained by remnant cholesterol causing atherosclerosis, a disease with a known inflammatory element. 14 Randomized, clinical trials have found that statin therapy prevents cardiovascular disease when CRP levels are increased, even if LDL cholesterol levels are below traditional intervention levels.…”
Section: Discussionmentioning
confidence: 76%
“…We have previously demonstrated that elevated remnant cholesterol is causally associated with increased risk of IHD and that this association is independent of low high-density lipoprotein cholesterol levels. 1,2 The causal association of nonfasting remnant cholesterol with low-grade inflammation observed in this study could be explained by remnant cholesterol causing atherosclerosis, a disease with a known inflammatory element. 14 Randomized, clinical trials have found that statin therapy prevents cardiovascular disease when CRP levels are increased, even if LDL cholesterol levels are below traditional intervention levels.…”
Section: Discussionmentioning
confidence: 76%
“…In a cohort of >50 000 Danish participants, Jorgensen et al identified genetic variants that contributed to extreme elevations in TG levels 29. The investigators showed that these genetic elevations in calculated RLP‐C based on nonfasting TG levels were associated with an 87% increased odds of MI.…”
Section: Discussionmentioning
confidence: 99%
“…96,97 Furthermore, recent genetic data support the contention that elevated TG levels are a direct cause of CV disease. 76,88 Recent studies suggest that non-fasting TGs may carry information regarding remnant lipoproteins associated with increased risk. 76,86,98,99 For general screening and risk evaluation, non-fasting…”
Section: Triglyceridesmentioning
confidence: 99%
“…76,88 Recent studies suggest that non-fasting TGs may carry information regarding remnant lipoproteins associated with increased risk. 76,86,98,99 For general screening and risk evaluation, non-fasting…”
Section: Triglyceridesmentioning
confidence: 99%